2019
DOI: 10.1038/s41598-019-56934-6
|View full text |Cite
|
Sign up to set email alerts
|

A prospective three-year follow-up study on the clinical significance of anti-neuronal antibodies in acute psychiatric disorders

Abstract: The clinical significance of anti-neuronal antibodies for psychiatric disorders is controversial. We investigated if a positive anti-neuronal antibody status at admission to acute psychiatric inpatient care was associated with a more severe neuropsychiatric phenotype and more frequent abnormalities during clinical work-up three years later. patients admitted to acute psychiatric inpatient care who tested positive for N-methyl-D-aspartate receptor (NMDAR), contactin-associated protein 2 (CASPR2) and/or glutamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…They thought autoimmune encephalitis associated with anti‐neuronal antibodies may be challenging to distinguish from primary psychiatric disorders. In contrast, another study showed anti‐neuronal antibody‐positive status during index admission was associated with more severe symptoms of depression, psychoticism and agitation at 3‐year follow‐up, 39 which supported anti‐neuronal antibodies may be of clinical significance in a subgroup of psychiatric patients. It was worth noting all of our patients' neurological symptoms were mild to moderate which restricted to headache, sleeping disorder, anxiety, and depression; none of our patients showed severe neurological symptoms like epilepsy or schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…They thought autoimmune encephalitis associated with anti‐neuronal antibodies may be challenging to distinguish from primary psychiatric disorders. In contrast, another study showed anti‐neuronal antibody‐positive status during index admission was associated with more severe symptoms of depression, psychoticism and agitation at 3‐year follow‐up, 39 which supported anti‐neuronal antibodies may be of clinical significance in a subgroup of psychiatric patients. It was worth noting all of our patients' neurological symptoms were mild to moderate which restricted to headache, sleeping disorder, anxiety, and depression; none of our patients showed severe neurological symptoms like epilepsy or schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…As we have shown in our review, the same idea may be applicable to purely psychotic AB-positive patients, including even those with ABs against NMDAR NR2 subunit. Some case reports and follow-up studies proved there was a difference between AB titers in acute and more stable phases [96, 97], but further research is certainly required to confirm and clarify the peculiarities of this correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were tested positive for IgG ABs in serum, but not CSF, mostly had only psychiatric symptoms and were successfully treated with antipsychotic medications [98]. Schou et al [96] conducted a follow-up study among patients who were tested positive in serum at admission to the acute psychiatric ward. None of them developed autoimmune encephalitis and all were treated as usual, but AB-positive status during admission was associated with more severe symptoms of depression, psychoticism, and agitation at 3-year follow-up [96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical psychiatry, only rarely has this iterative process led to genuine breakthroughs. Limited examples do exist for various kinds of mood disorders, including: (1) delineation of “vascular depression” among older adults with a first onset of depression in later life after specific cerebrovascular lesions 1 ; (2) onset of depressive disorders after specific infections 2 or the introduction of immune‐active therapies 3 ; and (3) recognition of “atypical” mood disorders in young adults with antineuronal antibodies 4 . The latter discovery has led to the use of immune therapies targeted to underlying pathophysiology 5 .…”
Section: Introductionmentioning
confidence: 99%